ANALISIS INVESTASI DANA HAJI DALAM PEMBIAYAAN INFRASTRUKTUR DAN PENINGKATAN KUALITAS PENYELENGGARAAN IBADAH HAJI - M. Zainul Abidin (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2016)
This paper analyzes the management of the Hajj funds for financing the infrastructure to improve the system of hajj services. The method used for this study is desk research or literature review. Based on the results of the research, it is known that the management of the Hajj funds can be invested to support for financing the infrastructure because the Hajj funds have the characterisics as funds deposited (safekeeping of a deposit) so as to resemble Islamic principles namely wadiah yadh dhamanah. It makes it possible for funds managers (BPKH) to optimize the benefit of Hajj funds and should prioritize the security of the funds. Based on Law 34/2014, the investment of Hajj funds in financing the infrastructure is intended to make the most of benefits to improve of the quality of hajj services and management with emphasis on security aspects of Hajj funds.